HUBUNGAN JENIS DAN LAMA PENGGUNAAN ALAT KONTRASEPSI HORMONAL TERHADAP GANGGUAN MENSTRUASI PADA IBU PUS DI KELURAHAN BINJAI KECAMATAN MEDAN DENAI KOTA MEDAN TAHUN 2014 - Febria Octasari; Sori Muda Sarumpaet; Yusniwarti Yusad (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Prevention of maternal morbidity and mortality is the main reason for family planning programs. The survey showed that 62% of married women aged 15-49 years using a family planning method, most of them using modern contraceptive methods were 58% and 4% using the traditional method of contraception. The purpose of this research is to analyze association between the type and duration of use of hormonal contraceptives on menstrual disorders in Kelurahan Binjai Kecamatan Medan Denai 2014. Analytic study was observational, using cross-sectional design with 210 person as samples. The sampling technique was simple random sampling. The result of this research is the type of hormonal contraception that many in demand by the respondent is kind of 3-month injectable contraceptive with a percentage of 35,7%. The results of the bivariate analysis showed the type of hormone contraceptive associated with menstrual disorders (RP=3,07; 95% CI: 2,25-4,19)  longer menstrual disorders (RP=2,52; 95% CI: 1,85-3,42)  disruption of the menstrual cycle (RP=2,88; 95% CI: 2,13-3,89) spotting (RP=3,85; 95% CI: 2,24-6,60). Duration of use of menstrual disorders associated with long periods (RP=1,53; 95% CI: 1,17-2,03) and disruption of the menstrual cycle (RP=1,49; 95% CI: 1,17-1,91). Acceptor is expected to choose the right contraception and ask health worker about various contraceptives before choosing contraceptives.